Genotyping Microbial Communities with MIDAS2: From Metagenomic Reads to Allele Tables. Issue 12 (5th December 2022) - Zhao, Chunyu; Goldman, Miriam; Smith, Byron J.; Pollard, Katherine S.
Abstract: The Metagenomic Intra‐Species Diversity Analysis System 2 (MIDAS2) is a scalable pipeline that identifies single nucleotide variants and gene copy number variants in metagenomes using comprehensive reference databases built from public microbial genome collections (metagenotyping). MIDAS2 is the first metagenotyping tool with functionality to control metagenomic read mapping filters and to customize the reference database to the microbial community, features that improve the precision and recall of detected variants. In this article we present four basic protocols for the most common use cases of MIDAS2, along with supporting protocols for installation and use. In addition, we provide in‐depth guidance on adjusting command line parameters, editing the reference database, optimizing hardware utilization, and understanding the metagenotyping results. All the steps of metagenotyping, from raw sequencing reads to population genetic analysis, are demonstrated with example data in two downloadable sequencing libraries of single‐end metagenomic reads representing a mixture of multiple bacterial species. This set of protocols empowers users to accurately genotype hundreds of species in thousands of samples, providing rich genetic data for studying the evolution and strain‐level ecology of microbial communities. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Species prescreening Basic Protocol 2 : Download MIDAS reference database Basic Protocol 3 : Population single nucleotide variant calling Basic Protocol 4 : Pan‐genome copy number variant calling Support Protocol 1 : Installing MIDAS2 Support Protocol 2 : Command line inputs Support Protocol 3 : Metagenotyping with a custom collection of genomes Support Protocol 4 : Metagenotyping with advanced parameters